Prolonged use of antipsychotic medications in long-term aged care in Australia: a snapshot from the HALT project. (March 2020) - Harrison, Fleur; Cations, Monica; Jessop, Tiffany; Aerts, Liesbeth; Chenoweth, Lynn; Shell, Allan; Sachdev, Perminder; Hilmer, Sarah; Draper, Brian; Brodaty, Henry
ABSTRACT: Objectives: Use of antipsychotic drugs in long-term aged care (LTC) is prevalent and commonly exceeds the recommended duration, but contributors to this problem are not well understood. The objective of this study is to provide a snapshot of the features of and contributors to prolonged use of antipsychotic medications (>12 weeks) among a sample of LTC residents. Design: We present retrospective and baseline data collected for the Australian Halting Antipsychotic Use in Long-Term Care (HALT) single-arm longitudinal deprescribing trial. Setting: Twenty-four long-term care facilities in Sydney, Australia. Participants: The HALT study included 146 older people living in 24 Sydney LTC homes who had been prescribed a regular antipsychotic medication for at least 3 months at baseline. Measurements: Detailed file audit was conducted to identify the date and indication recorded at initial prescription, consenting practices, longitudinal course of prescribing, and recommendations for review of antipsychotic medication. Behavioural and psychological symptoms of dementia (BPSD) and functional dependence at baseline were assessed via LTC staff interview. Cognition at baseline was assessed in a participant interview (where possible). Results: Antipsychotics were prescribed for 2.2 years on average despite recommendations by a doctor or pharmacist for review in 62% of cases. Consent for antipsychotic prescription was accessible for only one case and contraindications for use were common. Longer use of antipsychotics was independently associated with higher dose of the antipsychotic drug and greater apathy, but not with other BPSD. Conclusion: Antipsychotic medications appeared to be prescribed in this sample as a maintenance treatment in the absence of active indicated symptoms and without informed consent. Standard interventions, including recommendations for review, had been insufficient to ensure evidence-based prescribing.